Cancer risk among HIV-exposed uninfected children in the United States. (1st March 2023) - Horner, Marie-Josèphe; Hazra, Rohan; Barnholtz-Sloan, Jill S.; Shiels, Meredith S.; Engels, Eric A.
Abstract : In utero exposure to didanosine was associated with increased risk of brain cancer in a French study. We used United States health department records to assess cancer risk among 13 617 children exposed to HIV in utero, who remained HIV-uninfected after birth (1990–2017). Risk of brain tumors was borderline elevated among these children (standardized incidence ratio 2.2, 95% confidence interval 0.8–4.8, P  = 0.12, based on six cases). Risk was not significantly increased for leukemia or other cancers.